Costa Rica, land of endless orchids - Karremans Lok, Adam Philip (2013)
With almost 1,600 reported species (Karremans et al. 2012), Costa Rica has one of the richest orchid floras in tropical America, currently surpassed in total species number only by Brazil, Colombia, Ecuador and Peru (Govaerts et al. 2011). However, with an area of only 19,691 square miles (51,000 km, Costa Rica is five to 150 times smaller than any of those countries and therefore probably has the highest orchid species-to-area ratio in the world.